German board-level employee representation in multinational companies: Patterns of transnational articulation. (September 2019) - Rosenbohm, Sophie; Haipeter, Thomas
We investigate codetermination on German supervisory boards of multinational companies and pose two questions. First, under what conditions does board-level representation constitute a power resource for employee representatives? Second, how does board-level representation articulate with European Works Councils? We conclude that factors related to corporate structure – head office location, the level at which supervisory boards are established – play a decisive role in determining the power resources available to employee representatives. Articulation with European Works Councils depends on the adoption of a strategic approach whereby German employee representatives deploy the power resources derived from national codetermination rights at the transnational level, or use the mechanisms of transnational employee representation to compensate where such national power resources are lacking.